Effects of subclinical hypothyroidism in type II diabetes mellitus patients on biochemical, coagulation, and fibrinolysis status - Yasir Abbas Atia; Suhad Taha Mohammed; Sarmad S. Abdullah; Ahmed Saad Abbas; Hayder Adnan Fawzi (Wolters Kluwer Medknow Publications, 2024)
The aim of the currnet study to examine the effect of subclinical hypothyroidism (SCH) in diabetic patients on coagulation parameters. This retrospective case-control study involves 130 patients diagnosed with type 2 diabetes mellitus (T2DM), divided into 65 T2DM with newly diagnosed SCH and 65 euthyroid (EUT) T2DM patients without SCH. Fibrinogen (FIB) was significantly higher in SCH (508.2 ± 63.0 mg/dL) than EUT (428.1 ± 44.8 mg/dL). In the SCH patients, FIB correlated with several parameters, such as age (β = 0.396), body mass index (β = 0.578), glycated hemoglobin (β = 0.281), and activated partial thromboplastin time (β = 0.276). In conclusion SCH in DM patients appears to increase the magnitude of coagulopathy.